EFECT OF FOREIGN EXCHANGE RATE FLUCTUATIONS ON NIGERIAN ECONOMY - UFOEZE, Lawrence Olisaemeka; OKUMA, N., Camilus; NWAKOBY, Clem; Alajekwu, Udoka Bernard (Annals of Spiru Haret University. Economic Series, 2018)
This study investigated the effect of exchange rate fluctuations on Nigerian economy. The fixed and floating exchange eras were compared to know the exchange rate system in which the economy has fairly better. The time period covered was 1970 to 2012. The study employed the ordinary least square (OLS) multiple regression technique for the analysis. The coefficient of determination (R2), F-test, t-test, beta and Durbin-Watson were used in the interpretation of the results. The resulted revealed that about 85% of the changes in macroeconomic indicators are explained in the fixed exchange era. In the floating exchange era, 99% was explained while the whole periods has 73% explanatory power, hence the floating exchange era (1986 to date) is more effective in explaining economic trend in Nigeria. Also, exchange rate has significant positive effect on GDP during the fixed exchange rate era and negative effect the eras floating and all-time; inflation has insignificant negative effect on GDP during the fixed exchange era; significant effect in floating era and significant negative effect in the all-time period; money supply has insignificant negative effect GDP in fixed exchange era; and significant positive effect during the floating and all-time period; and oil revenue has significant positive effect on the GDP in all the exchange rate regimes (floating, fixed and all-time) in Nigeria. The study thus conclude that exchange rate movement is a good indicator for monitoring Nigerian economic growth. So far exchange rate has always been a key economic indicator for Nigeria. The floating exchange period has outperformed the fixed exchange rate in terms of contribution inflation, money supply and oil revenue to economic growth. This indicate that the floating exchange rate has been a better economic regime for sustainable economic growth in Nigeria. From the findings, it is evident that oil revenue has positive effect in Nigeria and has remained the mainstay of the economy. It is thus recommended among other things that a positive exchange rate stock should be monitored regularly, so as not to allow those that find exchange rate as an avenue of investment like banks and public carry out their business, which is more devastating to the economy.